"Identification of alkaloid compounds as potent inhibitors of Mycobacterium tuberculosis NadD using computational strategies". (May 2023) - Verma, Abhishek Kumar; Dubey, Saumya; Srivastava, Sandeep Kumar
Abstract: Mycobacterium tuberculosis is leading cause of death worldwide. NAD participates in a host of redox reactions in energy landscape of organisms. Several studies implicate surrogate energy pathways involving NAD pools as important in survival of active as well as dormant mycobacteria. One of the NAD metabolic pathway enzyme, nicotinate mononucleotide adenylyltransferase (NadD) is indispensable in mycobacterial NAD metabolism and is perceived as an attractive drug target in pathogen. In this study, we have employed in silico screening, simulation and MM-PBSA strategies to identify potentially important alkaloid compounds against mycobacterial NadD for structure-based inhibitor development. We have performed an exhaustive structure-based virtual screening of an alkaloid library, ADMET, DFT profiling followed by Molecular Dynamics (MD) simulation, and Molecular Mechanics-Poisson Boltzmann Surface Area (MM-PBSA) calculation to identify 10 compounds which exhibit favourable drug like properties and interactions. Interaction energies of these 10 alkaloid molecules range between −190 kJ/mol and -250 kJ/mol. These compounds could be promising starting point in the development of selective inhibitors against Mycobacterium tuberculosis . Graphical abstract: Cheminformatics research methodology template for forecasting possible anti-tubercular drugs. The Selleckchem Database's 20210731-L7900-Alkaloid-Compound-Library were evaluated against the mtb NadD enzyme. A total of 30 hits were chosen for further examination. The characterisation of the protein-ligand complex, structural investigations, biological activity projections, and MD simulations are examples of methods. Image 1 Highlights: Secondary energy pathways are attractive targets in mycobacteria to design novel drug leads. Ten alkaloids are proposed as potential hits against the Mtb NadD enzyme using in silico docking and simulation analysis. Hydroprotopine can be prioritized in pharmacophore-based drug design strategies against Mtb NadD.